Mass-selected ion beam generation using two rotating electric-field mass separation technique - Masashi Nojima (AIP Advances, 2023)
This paper describes the origin, principles, practical applications, and future perspectives of mass-selected ion beams generated using two rotating electric-field mass (REF-MS) filters. Our team has been investigating the underlying principles of REF-MS separation and assessing the feasibility of developing suitable systems to realize mass separation and ion beam convergence using rotating electric fields as well as the practicability of this method. This paper focuses on the mechanism underlying the observed cycloid trajectories followed by REF-MS-selected ions. A focused ion beam column with Ga and AuGe liquid metal ion sources (LMISs) was connected to REF-MS optics to assess the mass-selection performance of the filter. The mass-separation ability of this system was demonstrated by the ion projection images of Ga-LMIS (69Ga+ and 71Ga+) and AuGe-LMIS (97Au2+, Au2Ge+, and Au2Ge2+). The column was then replaced with a vacuum electrospray ionization (ESI) source. The size-selected water-cluster ion beams [(H2O)nH]+ were separated based on cluster size, and a microscale crater was created. Co-containing molecular ion beams were revealed using different concentrations of ESI sources, and a mass-separated [Co(DEGBE)4]+ ion beam was constructed.